2011
DOI: 10.1111/j.1749-6632.2011.06210.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the orbitofrontal cortex signal value?

Abstract: The orbitofrontal cortex (OFC) has long been implicated in associative learning. Early work by Mishkin and Rolls showed that the OFC was critical for rapid changes in learned behavior, a role that was reflected in the encoding of associative information by orbitofrontal neurons. Over the years, new data—particularly neurophysiological data—have increasingly emphasized the OFC in signaling actual value. These signals have been reported to vary according to internal preferences and judgments and to even be compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(176 citation statements)
references
References 86 publications
5
167
4
Order By: Relevance
“…The tests conducted on phase two showed that control subjects perform better in blocks 7, 9, 10 and 11 (all p<0.05). The results of this study can be correlated to the hypothesis that the orbitofrontal cortex has integrative function to signaling signals of reward/punishment for our actions and are able to detect and analyze details pertaining the overall situation [20]. To analyze the association between the severity of major depressive disorder and performance in the test, the authors examined the Beck Depression Inventory (BDI) scores in each of the blocks in this group.…”
Section: Executive Functions In Adults With Depressionmentioning
confidence: 86%
“…The tests conducted on phase two showed that control subjects perform better in blocks 7, 9, 10 and 11 (all p<0.05). The results of this study can be correlated to the hypothesis that the orbitofrontal cortex has integrative function to signaling signals of reward/punishment for our actions and are able to detect and analyze details pertaining the overall situation [20]. To analyze the association between the severity of major depressive disorder and performance in the test, the authors examined the Beck Depression Inventory (BDI) scores in each of the blocks in this group.…”
Section: Executive Functions In Adults With Depressionmentioning
confidence: 86%
“…Specifically, we propose that the medial PFC contributes to hippocampal valuation of novelty's biological salience, as this region has been implicated in the assessment of environmental novelty and the behavioral ramifications of its presence (Rangel and Hare 2010;Grabenhorst and Rolls 2011;Schoenbaum et al 2011;Silvetti et al 2011;Roy et al 2012). The medial PFC and other regions in the MTL, critically, predict habituation and extinction of behavioral responses to other biologically salient stimuli, such as fear-predicting stimuli (Vertes 2006;Schiller and Delgado 2010).…”
Section: Hippocampal Connectivity During Habituation To Noveltymentioning
confidence: 99%
“…The medial orbitofrontal cortex shares extensive reciprocal connections with the amygdala (Barbas et al, 2007), and both are central to emotional processing, particularly in evaluating salience aspects of the environment that guide emotional learning and promote adaptive behaviour (Adolphs et al, 1995;Rolls, 1996;Schoenbaum et al, 2011). Moreover, the connectivity of both, the amygdala as well as the orbitofrontal cortex includes reciprocal connections with the hippocampal formation, including the parahippocampus, and these pathways have been suggested to fundamentally contribute to the impact of emotional salience on learning (Cavada et al, 2000).…”
Section: Valence-specific Effects Of Ketaminementioning
confidence: 99%